2021
DOI: 10.3389/fcell.2021.676911
|View full text |Cite
|
Sign up to set email alerts
|

Length of the Neurogenic Period—A Key Determinant for the Generation of Upper-Layer Neurons During Neocortex Development and Evolution

Abstract: The neocortex, a six-layer neuronal brain structure that arose during the evolution of, and is unique to, mammals, is the seat of higher order brain functions responsible for human cognitive abilities. Despite its recent evolutionary origin, it shows a striking variability in size and folding complexity even among closely related mammalian species. In most mammals, cortical neurogenesis occurs prenatally, and its length correlates with the length of gestation. The evolutionary expansion of the neocortex, notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 218 publications
(419 reference statements)
1
30
0
Order By: Relevance
“…In these animals, the BP of the SVZ can sustain multiple rounds of divisions to generate other precursor cells before dividing into neurons ( Götz and Huttner, 2005 ; Lui et al, 2011 ; Florio and Huttner, 2014 ). Indeed, the increase in the number of the BP outer RG cells (oRG) originating from aRG, and their proliferative potential has been proposed as a contributor for the increase in cortex size ( Nonaka-Kinoshita et al, 2013 ; Fernández et al, 2016 ), but it does not seem to be sufficient, given the presence of lissencephalic animals with a high number of BP ( Kelava et al, 2013 ; Stepien et al, 2021 ). Seminal works in the past years have demonstrated that a variety of morphology exists among BP cells even in the same species and that this instead might be a key factor determining neocortical expansion ( Betizeau et al, 2013 ; Kalebic et al, 2019 ).…”
Section: Patterning Regionalization and Precursor Cell Typesmentioning
confidence: 99%
See 3 more Smart Citations
“…In these animals, the BP of the SVZ can sustain multiple rounds of divisions to generate other precursor cells before dividing into neurons ( Götz and Huttner, 2005 ; Lui et al, 2011 ; Florio and Huttner, 2014 ). Indeed, the increase in the number of the BP outer RG cells (oRG) originating from aRG, and their proliferative potential has been proposed as a contributor for the increase in cortex size ( Nonaka-Kinoshita et al, 2013 ; Fernández et al, 2016 ), but it does not seem to be sufficient, given the presence of lissencephalic animals with a high number of BP ( Kelava et al, 2013 ; Stepien et al, 2021 ). Seminal works in the past years have demonstrated that a variety of morphology exists among BP cells even in the same species and that this instead might be a key factor determining neocortical expansion ( Betizeau et al, 2013 ; Kalebic et al, 2019 ).…”
Section: Patterning Regionalization and Precursor Cell Typesmentioning
confidence: 99%
“…Sustained gliogenesis in the outer SVZ has been implicated in the expansion of the neuropile, and therefore, the neocortex convolutions in primates ( Rash et al, 2019 ). Of note, the genetic bases of such peculiarity of precursor cell types for neocortex expansion are mapped using gyrencephalic models ( Florio et al, 2015 , 2016 ; Cárdenas and Borrell, 2020 ; Heide et al, 2020 ; Stepien et al, 2021 ). At the signaling level, a number of pro-proliferative molecules from -and interacting with-the ECM niche of the progenitor pool, likely involving Pi3K-AkT, mTOR, and MAPK signaling pathways, is being recognized as a crucial trigger for the distinctive proliferative capacity of BP cells as well as for their positioning in the developing cortex ( Sheppard and Pearlman, 1997 ; Fietz et al, 2012 ; Moreno-Layseca and Streuli, 2014 ; Cavallin et al, 2018 ; Heinzen et al, 2018 ; Long et al, 2018 ; Kalebic et al, 2019 ; Subramanian et al, 2020 ; Kyrousi et al, 2021 ).…”
Section: Patterning Regionalization and Precursor Cell Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…The resultant model predicts that the timing of the switch from proliferative to neurogenic divisions produces the highest variation in final cortical numbers and is therefore potentially a strong driver of final brain morphology between species [Picco et al, 2018]. It is therefore clear that the timing and kinetics of neurogenesis vary across extant species, and that these changes correlate with altered brain morphology [Iwata, 2021;Stepien et al, 2021]. The causative role of these relationships can be inferred from experimental manipulations within the mouse, e.g.…”
Section: Models Of Timing Influencing Species-specific Parameters Of ...mentioning
confidence: 99%